2008
DOI: 10.1007/s10725-008-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators and sucrose on post harvest physiology, membrane stability and vase life of cut spikes of gladiolus

Abstract: Effects of post-harvest application of two plant growth regulators viz., gibberellic acid (GA 3 ) and benzyl adenine (BA) with sucrose in the vase solution on cell membrane stability and vase life of gladiolus were investigated. The vase solution treatment combinations of GA 3 and BA with sucrose significantly increased the membrane stability index and enhanced the vase life as compared to the sucrose alone treatments or the controls. Vase solution treatment of GA 3 (50 mg l -1 ), followed by BA (50 mg l -1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 28 publications
8
45
0
2
Order By: Relevance
“…The use of 1 mM fluridone did not influence the longevity of the stems, which was 5 days, compared with the 5.2 days of control flowers. Singh et al (2008) and Faraji et al (2011) also found increased gladiolus vase life when treated with GA 3 . According to Hunter et al (2004), the senescence rate can be changed with a variation in the relative concentrations of GA 3 and ABA in the flower tissue.…”
Section: Stem Longevitymentioning
confidence: 91%
“…The use of 1 mM fluridone did not influence the longevity of the stems, which was 5 days, compared with the 5.2 days of control flowers. Singh et al (2008) and Faraji et al (2011) also found increased gladiolus vase life when treated with GA 3 . According to Hunter et al (2004), the senescence rate can be changed with a variation in the relative concentrations of GA 3 and ABA in the flower tissue.…”
Section: Stem Longevitymentioning
confidence: 91%
“…The effect of treatment with DIC on membrane integrity is determined for seeds germinating according to the method of Singh [24] [25]. This parameter has been included in order to have more information about the stability of the membrane and the relative ion content.…”
Section: The Membrane Integritymentioning
confidence: 99%
“…After cooling to room temperature, electrical conductivity (value B) was measured again. Potassium chloride (0.01 mM) was used as standard, which gives specific conductance of 1.41 dS m SINGH et al, 2008) Water relations. Solution uptake was obtained by difference between initial and each evaluation day volume recorded using graduated cylinder.…”
Section: Inflorescences Of Gladiolus (Gladiolus X Hortulanus)mentioning
confidence: 99%
“…The lowest quantity of fully-open flowers in the sucrose solution alone and polymeric biguanide treatments, may have caused a lower solution uptake and a negative water balance, because water and carbohydrates are necessary for postharvest development of inflorescences (SINGH et al, 2008).…”
Section: Water Relationsmentioning
confidence: 99%
See 1 more Smart Citation